Gynura procumbens ethanol extract improves vascular dysfunction by suppressing inflammation in postmenopausal rats fed a high-fat diet - Khuzaidatul Azidah Ahmad Nazri; Qodriyah Haji Mohd Saad; Norsyahida Mohd Fauzi; Fhataheya Buang; Ibrahim Jantan; Zakiah Jubri (Taylor & Francis Group, 2021)
Context Gynura procumbens (Lour.) Merr. (Asteraceae) has been reported to have various pharmacological activities including anti-inflammatory effects. Objective This study sought to determine whether Gynura procumbens (GP) could improve vascular reactivity by suppressing inflammation in postmenopausal rats fed with five-times heated palm oil (5HPO) diet. Materials and methods Forty-eight female Sprague-Dawley rats were randomly divided into sham [non-ovariectomized; grouped as control, GP extracts (250 and 500 mg/kg), atorvastatin (ATV, 10 mg/kg)] and postmenopausal (PM) groups [ovariectomized rats fed with 5HPO; grouped as PM, GP extracts (250 and 500 mg/kg) and ATV (10 mg/kg)]. Each group (n = 6) was either supplemented with GP extract or ATV orally once daily for 6 months. Results In comparison with the untreated PM group, 250 and 500 mg/kg GP supplementation to PM groups reduced the systolic blood pressure (103 ± 2.7, 86 ± 2.4 vs. 156 ± 7.83 mmHg, p < 0.05), intima-media thickness (101.28 ± 3.4, 93.91 ± 2.93 vs. 143.78 ± 3.31 µM), vasoconstriction percentage induced by phenylephrine (102.5%, 88.3%, vs. 51.8%), sICAM-1 (0.49, 0.26 vs. 0.56 pg/mL) and sVCAM-1 (0.39, 0.25 vs. 0.45 pg/mL). GP extract supplementation increased vasorelaxation percentage induced by acetylcholine (78.4% vs. 47.3%) and sodium nitroprusside (84.2% vs. 53.7%), increased changes in plasma nitric oxide level (1.25%, 1.31% vs. 1.9%), and suppressed the elevation of TNF-α (0.39 vs. 1.02 pg/mL), IL-6 (0.43 vs. 0.77 pg/mL) and CRP (0.29 vs. 0.69 ng/mL) in the PM groups. Conclusions GP extract might improve vascular dysfunction by suppressing the inflammatory response, consequently preventing blood pressure elevation.